A new concept for marine environmental sustainability through recovery of magnesium carbonate from traditional salt production wastewater - Mirna Apriani; Wahyono Hadi; Ali Masduqi (Sustinere: Journal of Environment and Sustainability, 2018)
Environmental sustainability influenced social and economy sustainability. Without sustainably productive environment to provide resource foundation, it would difficult having sustainable society. Sustainable economy depends on sustainable raw material, energy and environmental resources. This work discussed about environmental sustainability in marine especially utilizing sea water as raw material for salt. This work started to investigate raw material characteristics and salt quality. The raw material characteristics represented high concentration for sodium, chloride, calcium and polluted by trace metal. According SEM-EDX result, salt contains lead and cooper. Salt farmer income is influenced by the salt quality, the higher its quality the bigger income received. Indirectly, economy in coastal was influenced by sea water quality. This is what encourages the research to achieve marine environmental sustainability in coastal area. The aims of this study are to review and categorize indicator for marine environmental sustainability into Driver-Pressure-States-Impacts-Response (DPSIR) and provide strategies suggestion for support environmental sustainability. DPSIR indicators are utilizing sea water, wastewater discharge into sea, increasing of sea water ion concentration, mangrove growth disruption, regulation for salt wastewater disposal direct to the sea. Recovery magnesium from salt wastewater is potential strategy to protect marine environment and to support economy-social sustainability.